Graphene Derivative As a Highly Efficient Nitrosonium Source: A Reusable Catalyst for Diazotization and Coupling Reaction. Issue 21 (16th December 2016) - Pethsangave, Dattatray A.; Khose, Rahul V.; Chaskar, Atul C.; Jun, Seong Chan; Some, Surajit
Abstract: An efficient and a simple approach for the synthesis of azo dyes have been developed by the diazo coupling reactions of active aromatic compounds in the presence of in‐situ nitrite functionalized graphene oxide polyvinyl alcohol GO‐PVA composite as a highly efficient nitrosonium ion source. This methodology was objected to defeat the limitations of the earlier reported method such as use of acids, alkalis and toxic solvents, to reduce the stability of diazonium salts at room temperature, modest yields and long reaction time. Additionally, the attractive advantages of the process are that it incorporated mild conditions with excellent yield, simple product isolation process, fastest reaction time and recyclability of catalyst. The isolated products were characterized by FT‐IR spectrum, UV‐spectroscopy and 1H‐NMR. The as‐prepared composites were confirmed by UV‐Visible, XRD, XPS, FT‐IR spectrum, SEM and TGA analysis. Abstract : In this work, we have reported nitrite functionalized GO‐PVA as nitrosonium source for the synthesis of azo dyes. The catalyst prepared by a simple method, which is able to reuse for several cycles without any efficiency loss. It is a simple and an efficient route for the synthesis of azo dyes with wider substrate scope. Reusability of the catalyst and shorter reaction time are the added advantages of this protocol.